3(12+10)=36x-8

Simple and best practice solution for 3(12+10)=36x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(12+10)=36x-8 equation:


Simplifying
3(12 + 10) = 36x + -8

Combine like terms: 12 + 10 = 22
3(22) = 36x + -8

Multiply 3 * 22
66 = 36x + -8

Reorder the terms:
66 = -8 + 36x

Solving
66 = -8 + 36x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36x' to each side of the equation.
66 + -36x = -8 + 36x + -36x

Combine like terms: 36x + -36x = 0
66 + -36x = -8 + 0
66 + -36x = -8

Add '-66' to each side of the equation.
66 + -66 + -36x = -8 + -66

Combine like terms: 66 + -66 = 0
0 + -36x = -8 + -66
-36x = -8 + -66

Combine like terms: -8 + -66 = -74
-36x = -74

Divide each side by '-36'.
x = 2.055555556

Simplifying
x = 2.055555556

See similar equations:

| x-.25x=30 | | 11x+4=11x-9 | | 6-x=4x-9 | | 1.5x+4.1=-2.8 | | 12+2x=p | | -14.5=-0.2+2.6 | | 6x^3=7x-1 | | 20x-5x+5=0 | | 7(2x+7)=14x+49 | | -8k^2-3k-4=0 | | -6=2+5x-6x | | 4(a-7)=-44 | | 2n+7=4n+8 | | -2(3x+5)=6-19x | | 2(x^2-5)(x-2)=0 | | 0=(0.3t^2)-6t+30 | | 9-m=3.5 | | -3(4s-6)-18=-2(9s+3)-3 | | 5(h-3)+2h+12= | | (y-5)(110)= | | X+140.00=0.05x | | 7=-5p+4p | | x^2+6x+5=2y-18 | | -1=-x+2 | | logy=5x+6 | | 6x+15=69x-30 | | 3x+19=-2x | | 4x-6x=7x-9+4x | | x.x-2x-3=x.x | | 7n^2-30n+2=-6 | | 15-(2m+7)=3+3m-15 | | 2c-6+4=32 |

Equations solver categories